2021
DOI: 10.1371/journal.pone.0258491
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in the postpartum period causes damage to the mammary gland

Abstract: Mastitis is an inflammation of the mammary gland in the breast and is typically due to bacterial infection. In malaria-endemic areas, mastitis with accompanying fever can be challenging to differentiate from malaria. At the same time, it is unclear whether malaria infection is directly involved in the development of mastitis. In the present study, whether mastitis develops during infection with malaria parasites was investigated using a rodent malaria model with Plasmodium berghei (P. berghei; Pb) ANKA. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Accurate and early diagnosis of malaria infection remains the key to malaria elimination in malaria-endemic areas as early and efective treatment really on this aspect. Nevertheless, to achieve the zero-malaria elimination goal [17], In general, the study percentage of malaria detected by nested PCR was higher (99.25%) compared to the percentage by TFM (11.17%) and RDT (77.23%). Tis was in agreement with the well-known improved sensitivity of PCR for malaria detection [34][35][36], as well as establishing the presence of submicroscopic illnesses in the population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Accurate and early diagnosis of malaria infection remains the key to malaria elimination in malaria-endemic areas as early and efective treatment really on this aspect. Nevertheless, to achieve the zero-malaria elimination goal [17], In general, the study percentage of malaria detected by nested PCR was higher (99.25%) compared to the percentage by TFM (11.17%) and RDT (77.23%). Tis was in agreement with the well-known improved sensitivity of PCR for malaria detection [34][35][36], as well as establishing the presence of submicroscopic illnesses in the population.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, to achieve the zero-malaria elimination goal [17], efective tools for malaria diagnosis are needed as clinical diagnosis of this infection remains the key, before making an informed choice on antimalarial medication. It is therefore critical to assess current malaria diagnostic tools at the national level, particularly in resource-limited settings, to determine which tool is more suitable for the detection of malaria infection among pregnant women, as accurate diagnosis of this infection must be followed by immediate treatment, as studies have shown that malaria, particularly in pregnancy, is associated with postpartum complications such as mastitis [18], and excessive uterine blood loss [19].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins showing one or two peptide spectral matches (PSMs) were excluded. Protein levels were normalized to actin, cytoplasmic 1 (accession: P60710), as previously described [ 23 ]. The normalized experimental signal was calculated as follows: (observed experimental signal) ÷ (normalisation factor).…”
Section: Methodsmentioning
confidence: 99%